Seasonal Thermal Energy Storage with Aqueous Sodium Hydroxide – Development and Measurements on the Heat and Mass Exchangers. (November 2018) - Daguenet-Frick, Xavier; Dudita, Mihaela; Omlin, Lukas; Paul, Gantenbein
Abstract: A 1 kW closed sorption Thermal Energy Storage (TES) system based on water absorption/desorption in a high-energy density sorbent like sodium hydroxide (sorbent, NaOH) is developed and tested at HSR-SPF. The overall concept of the 1 kW prototype system, based on the tube bundle and falling film model is presented. A modular design was chosen for the absorber/desorber unit with the aim of testing several types of tubes and liquid sorbent modifications. The influence of SiC foams with different porosity on the sorbent mass uptake, thus on the sorbent residence time in the water vapour is presented. The experiments have indicated that, although a better residence time can be obtained for ceramic samples with small pores size, a balance has to be found between ceramic clogging and gas-liquid area to achieve an efficient heat and mass exchange. The improved tube bundles are further tested in the 1 kW prototype.